Comparative Analysis of Confucians Teachings Based on Morality and Legalism Based on Legal State Administration (Texas Journal of Philology, Culture and History, 2024)
The evolution of ancient Chinese philosophy and culture is examined in this article. Additionally, a comparison analysis is conducted between the morality-based Confucianism and the legislation-based Legism, both of which greatly influenced the Chinese people's worldview in ancient China